On the Concept of graffiti - Proehl, Kyle (Street Art & Urban Creativity, 2024)
In this article I present a series of reflections on the concept of graffiti. What begins as a critique of the ideological relation between “street art” and “graffiti” on the one hand and “center” and “periphery” on the other, unfolds as a schematic exploration of the relation between graffiti and social crisis. These theses argue that graffiti can and should be interpreted, and that this interpretation depends upon analyzing graffiti’s character as both text and image. In doing so they explore graffiti in crisis across the American hemisphere, moving from “center” to “periphery” and back again. In the ruin of New York, the commune of Oaxaca, the explosion of Santiago, we catch a vivid glimpse of the social form and latent content of graffiti.